AUDIT REPORT LAG: FAKTOR YANG MEMPENGARUHI - Jayati, Rima Dwi; Machmuddah, Zaky; Utomo, St. Dwiarso (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2020)
Obtaining evidence regarding audit report lag and influencing factors is the main objective of this study. All mining companies listed on the Indonesia Stock Exchange in the 2014-2018 period were made the population in this study. The purposive sampling technique was used as the basis for obtaining a representative sample, so that a sample of 15 companies was obtained. Multiple linear regression was used as an analytical tool in this study. Research findings prove that solvability has an influence on audit report lag. Whereas accounting income, audit opinion, and firm size do not have an influence on audit report lag.